Pemanfaatan Limbah Kulit Singkong untuk Produksi Oligosakarida melalui Hidrolisis Kimiawi - Sasongko, Ashadi; Lumbantobing, Deosdado Farrel H; Rifani, Agus (JST (Jurnal Sains Terapan), 2019)
Cassava peels are biomass wastes that is rich of polysaccharides. Polysaccharides can be hydrolyzed chemically under control to produce oligosaccharides. The aims of this research are to study the suitability of the type of acids and the concentration of acids to hydrolyze, and analize the hydrolysis product using spectrophotometer and thin layer chromatography (TLC). The acids used in the hydrolysis were chloride acid, sulphuric acid, phosphoric acid, acetic acid, and citric acid, in concentration 0.3; 0.4, 0.5; 0.6; 0.7 molar. Total sugar was determined using phenol method. Analysis of reducing sugar was performed by the DNS method. The ratio of total sugar to reducing sugar was used to predict the degree of polymerization (DP). Almost all of acids with each concentration produced DP 2-6. The results were also confirmed using TLC and the retardation factor (Rf) compared using glucose and maltose as relative standards.Keywords: cassava peel waste, oligosaccharide, chemical hydrolysis